Genomic-based root plasticity to enhance abiotic stress adaptation and edible yield in grain crops. (June 2020) - Dwivedi, Sangam L.; Stoddard, Frederick L.; Ortiz, Rodomiro
Graphical abstract: Highlights: Plants cope with environmental variability through plasticity. Plasticity traits are multigenic. Selection for high or low plasticity along with high or low trait performance feasible. Genetic cost associated with plasticity. Abstract: Phenotypic plasticity refers to changes expressed by a genotype across different environments and is one of the major means by which plants cope with environmental variability. Multi-fold differences in phenotypic plasticity have been noted across crops, with wild ancestors and landraces being more plastic than crops when under stress. Plasticity in response to abiotic stress adaptation, plant architecture, physio-reproductive and quality traits are multi-genic (QTL). Plasticity QTL (pQTL) were either collocated with main effect QTL and QEI (QTL × environment interaction) or located independently from the main effect QTL. For example, variations in root plasticity have been successfully introgressed to enhance abiotic stress adaptation in rice. The independence of genetic control of a trait and of its plasticity suggests that breeders may select for high or low plasticity in combination with high or low performance of economically important traits. Trait plasticity in stressful environments may be harnessed through breeding stress-tolerant crops. There exists a genetic cost associated with plasticity, so a better understanding of the trade-offs between plasticity and productivity is warranted prior to undertaking breeding for plasticity traits together with productivity in stress environments.